The art in digital testimonial narratives: a persuasive tool in communication for health - González-Cabrera, Catalina (2023)
This research explores, through a pre-experimental design, how artistic resources can contribute to health prevention. For this purpose, participants (N = 118) completed a pre-test questionnaire and, after interacting with four testimonial narratives in the COVID-19 Diaries website, specially developed for this research, responded to the post-test. The study investigated the role of art in prevention intention, risk perception, and behavior, as well as the association with narrative transportation and identification with characters, the two main mechanisms explaining narrative persuasion. The results demonstrated the importance of including artistic resources in health narratives and the mediating role of narrative transportation and identification with characters in risk perception during health crises. These findings are of theoretical and methodological importance for understanding the mechanisms of narrative persuasion in health communication research through digital storytelling.